Education for Sustainable Development Approach to Improving Environmental Awareness in Elementary School Ecosystem Materials - Ika Damayanti; Woro Sri Hastuti; Rashika Ardafa Sahila; Lutfiana Nurohmah (MIMBAR PGSD Undiksha, 2025)
Increasingly complex environmental problems require strengthening environmental literacy since elementary school so that students have awareness and responsibility for ecosystem sustainability. This study aims to analyze the effectiveness of implementing the Education for Sustainable Development (ESD) approach in improving students' environmental literacy and environmental care character in science learning. This study used a quasi-experimental method with a pretest-posttest control group design. The study population was fifth-grade elementary school students with a sample of 58 students selected using cluster random sampling techniques, consisting of an experimental class implementing the ESD approach and a control class using the Problem-Based Learning (PBL) model. Data were collected through observation sheets of learning implementation and environmental literacy instruments, then analyzed using t-test and N-Gain. The results showed that learning with the ESD approach was implemented with a score of 95% which is categorized as very good, significantly increasing students' environmental literacy and environmental care character, and was more effective than the PBL model. These findings indicate that the ESD approach can be used as an effective learning strategy to instill awareness, responsibility, and environmentally friendly behavior from an early age, so that the implications can strengthen sustainable education at the elementary school level.